Vivid Representation and Victims of Forced Displacement in Jewish Literature in Greek - Glas, Eelco (NTT, 2025)
This article examines the portrayal of forced displacement in selected Greek-language Jewish prose texts. The selected narratives concern 1) the capture of slaves from Judea by Ptolemy I and their liberation by his son (Arist. 12-27); 2) Ptolemy IV’s forced mobilisation of Jews to the hippodrome of Schedia, near Alexandria (3 Macc. 4:4-11); and 3) Mary of Bethezuba, a refugee in Jerusalem during the Roman siege in 70 CE (Josephus, J.W. 6.199-219). I analyse the role of non-hegemonic social groups such as women, children, and the elderly in these narratives in terms of Greco-Roman rhetorical conventions of vivid representation (enargeia). Based on this analysis, I argue that the emphasis on these specific groups can be explained as rhetorical highlights designed to appeal to the imagination of ancient readers and listeners.